Accuracy of coronary computed tomography angiography for bioresorbable scaffold luminal investigation: a comparison with optical coherence tomography - Carlos Collet (2018)
© 2016, Springer Science+Business Media Dordrecht. To establish the accuracy of coronary computed tomography angiography (CTA) for in-scaffold quantitative evaluation with optical coherence tomography (OCT) as a reference. The translucent backbone of the bioresorbable scaffold allow us to evaluate non-invasively the coronary lumen with coronary CTA. In the ABSORB first-in-man studies, coronary CTA was shown to be feasible for quantitative luminal assessment. Nevertheless, a comparison with an intravascular modality with higher resolution has never been performed. In the ABSORB Cohort B trial, 101 patient with non-complex lesions were treated with the fully biodegradable vascular scaffold. For this analysis, all patients who underwent coronary CTA at 18 months and OCT within ±180 days were included. Coronary CTA and OCT data were analysed at an independent core laboratory for quantitative cross-sectional luminal dimensions. The primary objective was the accuracy and precision of coronary CTA for in-scaffold minimal lumen area assessment, with OCT as a reference. Among the 101 patients of the ABSORB Cohort B trial, 35 underwent both OCT and coronary CTA. The feasibility of quantitative evaluation was 74%. In the scaffolded segment, coronary CTA underestimated minimal lumen area by 9.8% (accuracy 0.39 mm2, precision 1.0 mm2, 95% limits of agreement −1.71 to 2.50 mm2). A similar level of agreement was observed in the non-scaffolded segment. Compared to OCT, coronary CTA appears to be accurate for the estimation of in-scaffold luminal areas, with no difference compared to the non-scaffolded region.